How To Find Information : a Guide For Researchers. - Rumsey, Sally (McGraw-Hill International (UK) Ltd., 2008)
Helps researchers in finding, accessing and evaluating information for dissertations, projects or reports. This book works through the information-seeking process, from planning the search to evaluating and managing the end results. It also suggests how to do this efficiently and effectively whilst using a range of sources.